2017
DOI: 10.1159/000462153
|View full text |Cite
|
Sign up to set email alerts
|

A New Era of Systemic Therapy for Hepatocellular Carcinoma with Regorafenib and Lenvatinib

Abstract: HCC (BCLC-C), patients with intermediate-stage HCC (BCLC-B)were included in the SHARP study and the Asia Pacific study; therefore, sorafenib is a widely approved agent for systemic therapy not only for advanced-stage HCC but also for unresectable HCC (including intermediate-stage HCC). In fact, sorafenib is often administered to patients with intermediate-stage HCC (BCLC-B) in clinical practice and to 16.4-19.6% of patients in clinical trials worldwide [3][4][5] .The population of patients with intermediate-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…However, it is unclear whether TN patients have a life expectancy similar to that of patients who are migrated to sorafenib after failure of radical/locoregional therapies in routine clinical care, where provision of sorafenib does not strictly follow clinical trial eligibility criteria and often extends to subjects with a wider range of liver functional reserve and BCLC stage, variables that are likely to make the expected survival benefit from sorafenib dissimilar to that reported in phase III trial data [14,15]. Moreover, since the treatment landscape of HCC has recently expanded to include second-line therapies [16,17], it is important to understand whether treatment sequencing prior to sorafenib might influence the eligibility of patients to receive further systemic treatment lines following sorafenib discontinuation [18]. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether TN patients have a life expectancy similar to that of patients who are migrated to sorafenib after failure of radical/locoregional therapies in routine clinical care, where provision of sorafenib does not strictly follow clinical trial eligibility criteria and often extends to subjects with a wider range of liver functional reserve and BCLC stage, variables that are likely to make the expected survival benefit from sorafenib dissimilar to that reported in phase III trial data [14,15]. Moreover, since the treatment landscape of HCC has recently expanded to include second-line therapies [16,17], it is important to understand whether treatment sequencing prior to sorafenib might influence the eligibility of patients to receive further systemic treatment lines following sorafenib discontinuation [18]. …”
Section: Introductionmentioning
confidence: 99%
“…However, by analyzing the specific percentages of HCV-positive patients in each of the trial involved, we observed no statistical difference between HCV prevalence in the sorafenib group and in the comparator group (relative risk: 0.98; 95% CI: 0.86-1.11). On one side, this can reassure for the transitivity of the NMA with regard to HCV status, but on the other side we need to point out that the viral status should be considered when developing further meta-analytic approaches, such as the present NMA, with the possible access to completed trial data [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, the phase III REFLECT trial, involving 954 patients with unresectable HCC (January 25, 2017), achieved the primary end-point (overall survival) in the lenvatinib group, not inferior to that with sorafenib and with a longer, statistically superior, PFS [27,28]. At the time the present NMA was developed, results from the REFLECT trial were still not published, but considering the primary end-point (overall survival) it would be unlikely that lenvatinib inclusion would change present results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The BRISK-PS trial did not include alpha-fetoprotein as a stratification factor, which caused an unfavorable balance against the trial drug similar to that seen in the REFLECT trial [11]. The RESORCE trial led to the inclusion of vascular invasion as an independent stratification factor and alpha-fetoprotein as a stratification factor in the design of trials of second-line drugs [21]. However, the CELESTIAL trial had a conventional design with few strategic elements (Table 6) and did not even exclude sorafenib-intolerant patients as in the RESORCE trial [2, 20, 21].…”
Section: Phase III Celestial Trialmentioning
confidence: 99%
“…The RESORCE trial led to the inclusion of vascular invasion as an independent stratification factor and alpha-fetoprotein as a stratification factor in the design of trials of second-line drugs [21]. However, the CELESTIAL trial had a conventional design with few strategic elements (Table 6) and did not even exclude sorafenib-intolerant patients as in the RESORCE trial [2, 20, 21]. The only inclusion criteria regarding prior treatment were (a) prior sorafenib treatment, (b) progression following at least 1 prior systemic treatment for HCC, and (c) up to 2 prior systemic regimens for advanced HCC; the exact number of sorafenib-intolerant patients enrolled remains unclear.…”
Section: Phase III Celestial Trialmentioning
confidence: 99%